Fiber vibration sensor multiplexing deploying KS code in SAC-OCDMA with direct decoding technique - Abiola, Taiwo Ambali (2014)
The advent of fiber optic vibration sensors has provided a way of achieving distributed sensing for remote vibration monitoring without being limited by electromagnetic effects and others which are hurdles faced in the conventional electrical sensors. Among the techniques that have been introduced for distributed vibration sensing are Time Division Multiplexing (TDM),Wavelength Division ultiplexing (WDM) and Optical Code Division Multiple Access (OCDMA). Some of these techniques are either not suitable for real time vibration monitoring due to low scanning speed or high cost of the required light source. OCDMA, which is known to be effect in providing information security, also has challenges with Multiple Access Interference (MAI) which makes it difficult to differentiate the correct signals from the interfering ones. Fiber vibration sensor multiplexing using Khazani-Syed (KS) code in Spectral Amplitude Coding Optical Code Division Multiplex (SAC/OCDMA) with direct decoding was investigated in this work. This was done in order to eliminate the MAI effects with less cost and complexity. The proposed work was carried out using a simulation tool to compare KS codes with Optical Orthogonal Code (OOC) and Modified Quadratic Congruence (MQC) codes while laboratory experiment was used to implement and compare the system based on the two decoding techniques and as well as with simplified WDM. The results show that the proposed system exhibits low noise level and capable of eliminating MAI when compared with complimentary decoding counterpart while still demonstrating low cost and complexity of achieving distributed vibration sensing over OOC and MQC codes. In addition, it demonstrates optimal performance as the received power level of up to 3.2 dB is measured above WDM based system. Therefore, the proposed system presents a better alternative for quasi distributed vibration monitoring. The range of frequency measured from 0 Hz to 401 Hz shows its suitability for structures that exhibit low frequency such has remote bridge, transformer, and pipeline vibration monitoring.